FG-coupled Fixed Point Theorems for Contractive and Generalized Quasi-contractive Mappings - Karichery, Deepa; Pulickakunnel, Shaini (Sarajevo Journal of Mathematics, 2024)
In this paper, we prove FG-coupled fixed point theorems for different contractive mappings and generalized quasi- contractive mappings in partially ordered complete metric spaces. We prove the existence of FG-coupled fixed points of continuous as well as discontinuous mappings. Our first three results generalize the theorems of Gnana Bhaskar and Lakshmikantham [T. Gnana Bhasakar, V. Lakshmikantham; Fixed point theorems in partially ordered metric spaces and applications, Nonlinear Anal. 65 (7) (2006) 1379-1393]. We give some examples to illustrate the results.